Exploring the Utilisation of Stand up Paddle Boarding in Australia - Ben Schram; James Furness (MDPI AG, 2017)
Stand Up Paddle Boarding (SUP) has grown exponentially in the last few years with unprecedented participation rates globally. Despite some scientific research on physiological and performance variables, minimal information exists regarding participation and utilisation. The purpose of this study was to discover more about how and where people participate in the relatively new sport of SUP. An open-source online survey application was administered internationally to active SUP participants to capture information relevant to both demographics and participation. Of a total of 240 responses, 154 (64.2%) were Australian. The average SUP rider was 42.9 ± 11.7 years, mass 80.4 ± 18.7 kg, 1.75 ± 0.10 m tall with a BMI of 26.1 ± 4.9. More males (69.5%) participate in SUP than females with the majority of participants from the eastern seaboard of Australia. Participants most commonly used SUP for fun and fitness, for around 3 h per week, predominantly at the beach with friends, with around half of the respondents reporting a competitive involvement. This is the first study to date to quantify participation of SUP within Australia. Results revealed SUP is a global activity with a high representation within Australia. Key findings from this study reveal the geographical and demographic distribution of SUP use. Consequently, these findings may inform the industry about its target audience. Additionally, information regarding the 'typical' SUP rider may serve to further promote and grow the sport.